Post-transcriptional control of haemostatic genes: mechanisms and emerging therapeutic concepts in thrombo-inflammatory disorders - Danckwardt, Sven; Trégouët, David-Alexandre; Castoldi, Elisabetta (Cardiovascular research, 2023)
Abstract The haemostatic system is pivotal to maintaining vascular integrity. Multiple components involved in blood coagulation have central functions in inflammation and immunity. A derailed haemostasis is common in prevalent pathologies such as sepsis, cardiovascular disorders, and lately, COVID-19. Physiological mechanisms limit the deleterious consequences of a hyperactivated haemostatic system through adaptive changes in gene expression. While this is mainly regulated at the level of transcription, co- and posttranscriptional mechanisms are increasingly perceived as central hubs governing multiple facets of the haemostatic system. This layer of regulation modulates the biogenesis of haemostatic components, for example in situations of increased turnover and demand. However, they can also be ‘hijacked’ in disease processes, thereby perpetuating and even causally entertaining associated pathologies. This review summarizes examples and emerging concepts that illustrate the importance of posttranscriptional mechanisms in haemostatic control and crosstalk with the immune system. It also discusses how such regulatory principles can be used to usher in new therapeutic concepts to combat global medical threats such as sepsis or cardiovascular disorders.